2000
DOI: 10.1542/peds.105.4.805
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Sedation Events in Pediatrics: A Critical Incident Analysis of Contributing Factors

Abstract: This study-a critical incident analysis-identifies several features associated with adverse sedation events and poor outcome. There were differences in outcomes for venue: adverse outcomes (permanent neurologic injury or death) occurred more frequently in a nonhospital-based facility, whereas successful outcomes (prolonged hospitalization or no harm) occurred more frequently in a hospital-based setting. Inadequate resuscitation was more often associated with a nonhospital-based setting. Inadequate and inconsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
232
1
19

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 506 publications
(259 citation statements)
references
References 85 publications
7
232
1
19
Order By: Relevance
“…Regulatory bodies have little influence on the care that patients receive outside the hospital or ambulatory care setting. After an evaluation of the Food and Drug Administration adverse drug event reporting system, Cote et al 15 reported that permanent neurologic injury or death occurred more frequently in a non-hospital-based facility (92.8% vs 37.2%). This study and others have clearly demonstrated that conscious sedation may rapidly progress to deep sedation and even general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory bodies have little influence on the care that patients receive outside the hospital or ambulatory care setting. After an evaluation of the Food and Drug Administration adverse drug event reporting system, Cote et al 15 reported that permanent neurologic injury or death occurred more frequently in a non-hospital-based facility (92.8% vs 37.2%). This study and others have clearly demonstrated that conscious sedation may rapidly progress to deep sedation and even general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Dichos datos están respaldados por estudios similares de sedación consciente para tratamiento estomatológico en niños a través de midazolam por vía oral (20,23), reconfi rmando la seguridad de la dosis utilizada por vía oral (25,26).…”
Section: Resultsunclassified
“…Cote et al reported on the adverse sedation events in children in a study published in 2000 (Cote, Notterman et al 2000). This study was a critical incident analysis of contributory factors.…”
Section: Sedation Related Complications and Their Managementmentioning
confidence: 96%